Event-Triggered Dynamic Quantization for Nonlinear Systems With One-Bit Data Transmission - Almakhles, Dhafer; Abdelrahim, Mahmoud (IEEE transactions on automatic control, 2024)
In this article, we study the problem of output feedback control for nonlinear systems under event-triggered implementation and dynamic quantization. We focus on the case where the initial output measurement is unknown and we propose a novel dynamic quantization policy to capture the output in a finite time. Next, the event-triggering mechanism that we design relies on a dynamic variable, which allows for reducing the amount of transmissions over the network. The dynamic quantizer is binary in the sense that the quantized output signal can be transmitted by using only a single bit. The encoding-decoding mechanism is provided in a systematic way such that the encoder-decoder pair realize a matching information on the quantized signal. The combined event-triggering condition and the dynamic quantizer guarantee asymptotic stability property for the closed-loop system. The Zeno behavior is prevented by means of the time-regularization technique. The efficiency of the proposed method is demonstrated on a numerical example.